2013
DOI: 10.1371/journal.pone.0067827
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Phylogeography of Sandy vs. Rocky Supralittoral Isopods in the Megadiverse and Geologically Dynamic Gulf of California and Adjacent Areas

Abstract: Phylogeographic studies of animals with low vagility and restricted to patchy habitats of the supralittoral zone, can uncover unknown diversity and shed light on processes that shaped evolution along a continent’s edge. The Pacific coast between southern California and central Mexico, including the megadiverse Gulf of California, offers a remarkable setting to study biological diversification in the supralittoral. A complex geological history coupled with cyclical fluctuations in temperature and sea level prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 76 publications
5
70
2
1
Order By: Relevance
“…This is in contrast to what has been found for supralittoral isopods of the genus Tylos , for which colonization of the northeastern Pacific appears to have proceeded from the Caribbean (Hurtado et al. , ). Paleontological studies of the Gulf of California report that most fauna‐rich sediments found in this region have affinities with Caribbean fauna (Escalona‐Alcázar et al.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This is in contrast to what has been found for supralittoral isopods of the genus Tylos , for which colonization of the northeastern Pacific appears to have proceeded from the Caribbean (Hurtado et al. , ). Paleontological studies of the Gulf of California report that most fauna‐rich sediments found in this region have affinities with Caribbean fauna (Escalona‐Alcázar et al.…”
Section: Discussioncontrasting
confidence: 79%
“…Third, we also examined whether populations of this isopod in the Gulf of California have closer affinities with lineages from the Caribbean, as has been observed for other coastal isopods (Hurtado et al. , ) and for marine fossils (Smith ; Escalona‐Alcázar et al. ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Juveniles of some species, however, may be able to surf by rolling themselves into a ball, potentially facilitating dispersal among nearby beaches [7], [15]. Consistent with their biological characteristics, high levels of population genetic differentiation have been observed at small geographic scales in members of Tylos , implying that surrounding unsuitable habitats constitute effective dispersal barriers and that the potential for population isolation is high [9]. Furthermore, factors that can dramatically modify the distribution of coastline habitats, such as tectonic activity and eustatic sea level fluctuations, as well as climate change, appear to strongly influence the evolutionary histories of these isopods [9].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, littoral isopod species have been considered as good disperses (Vandel, ). Nevertheless, recent phylogeographic studies on the supralittoral isopod genera Tylos Audouin, 1826 and Ligia Fabricius, 1798, have revealed highly structured populations and deep divergences among multiple regional lineages (Hurtado et al ., , ; Markow & Pfeiler, ; Eberl et al ., ). Our results support in part this latter observation.…”
Section: Discussionmentioning
confidence: 99%